THE ROLE OF PHYSICAL ACTIVITY AND DIETARY HABITS IN PREVENTING OBESITY IN ADULTHOOD - Mihaela Jurdana; Ana Petelin; Maša Černelič Bizjak; Mojca Bizjak; Tadeja Jakus; Zala Jenko Pražnikar (Annales Kinesiologiae, 2013)
Purpose: The paper discusses the evidence linking physical inactivity and dietary habits with obesity. The hypothesis is that low levels of physical activity and sedentary lifestyles favour a positive energy balance, therefore leading to obesity, low grade inflammation and weight gain.